Peter the Great’s “heirs”: power and administration in post-Petrine Russia - N. A. Omelchenko (Вестник университета)
The article examines the evolution of the power and governance system in the first decade after the death of Peter the Great, one of the most dramatic periods of Russian history, commonly referred to in the historical literature as the “ epoch of palace coups”. The article gives the author’s interpretation of the activities of the Supreme Privy Council to improve public administration during the reign of Catherine I and Peter II. Particular attention is paid to the analysis of events connected with the invitation to the Russian throne by the members of Supreme Privy Council of the niece of Peter the Great, the Duchess of Courland Anna Ioannovna, during whose reign the first attempt in the political history of Russia was made to limit the autocratic power of the monarch. The author examines the reasons for the defeat of the plan of the “supreme leaders”, who proposed to Anna Ioannovna “restrictive points” (“conditions”), formulated by Prince D.M. Golitsyn, to change the form of government in Russia, and draws some important conclusions for understanding the events. According to the author, Anna Ioannovna managed to snatch victory, relying on the support of the middle and lower nobility, primary because in Russia the middle class was always afraid of the weakening of the central government, which, as a rule, led either to anarchy or to the power of the oligarchy.